Peran Asrama Sahabat Yatim Medan Aksara Dalam Mengembangkan Potensi dan Kepercayaan Diri Anak Asuh - N, Nurmayani; Zahra, Hafizha; Pratiwi, Indy; Sinaga, Anita; Asura, Miftah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines the role of Sahabat Yatim Medan Aksara Orphanage in fostering the potential and self-confidence of foster children. Orphans often face emotional, social, and educational challenges due to the loss of a parental figure. This qualitative research uses in-depth interviews and direct observation methods involving foster children, staff, and orphanage facilities. The results showed that the orphanage programs are designed to meet the physical, social, and emotional needs of the children through sports activities, arts, religious education, and emotional support from the caregivers. Children are given the opportunity to explore their interests and talents, improving their self-confidence and academic performance. Adequate facilities such as study rooms, a small library, and computers support their learning process. This study concludes that Sahabat Yatim Medan Aksara Orphanage plays an important role in creating a safe and supportive environment for children's development. The study implies the importance of developing skills training programs and improving educational facilities to ensure the children's future success.